The disaster days - Behrens, Rebecca (Sourcebooks Young Readers, 2021)
Thirteen-year-old Hannah's first real babysitting job turns into a nightmare when a major earthquake knocks out power and phones, cuts off the island, and leaves her stranded with two children.